Applying antibody-sensitive hypervariable region 1-deleted hepatitis C virus to the study of escape pathways of neutralizing human monoclonal antibody AR5A - Velázquez-Moctezuma, Rodrigo (PLoS Pathog, 2017)
Hepatitis C virus (HCV) is a major cause of end-stage liver diseases. With 3–4 million new HCV infections yearly, a vaccine is urgently needed. A better understanding of virus escape from neutralizing antibodies and their corresponding epitopes are important for this effort. However, for viral isolates with high antibody resistance, or antibodies with moderate potency, it remains challenging to induce escape mutations in vitro. Here, as proof-of-concept, we used antibody-sensitive HVR1-deleted (ΔHVR1) viruses to generate escape mutants for a human monoclonal antibody, AR5A, targeting a rare cross-genotype conserved epitope. By analyzing the genotype 1a envelope proteins (E1/E2) of recovered Core-NS2 recombinant H77/JFH1(ΔHVR1) and performing reverse genetic studies we found that resistance to AR5A was caused by substitution L665W, also conferring resistance to the parental H77/JFH1. The mutation did not induce viral fitness loss, but abrogated AR5A binding to HCV particles and intracellular E1/E2 complexes. Culturing J6/JFH1(ΔHVR1) (genotype 2a), for which fitness was decreased by L665W, with AR5A generated AR5A-resistant viruses with the substitutions I345V, L665S, and S680T, which we introduced into J6/JFH1 and J6/JFH1(ΔHVR1). I345V increased fitness but had no effect on AR5A resistance. L665S impaired fitness and decreased AR5A sensitivity, while S680T combined with L665S compensated for fitness loss and decreased AR5A sensitivity even further. Interestingly, S680T alone had no fitness effect but sensitized the virus to AR5A. Of note, H77/JFH1(L665S) was non-viable. The resistance mutations did not affect cell-to-cell spread or E1/E2 interactions. Finally, introducing L665W, identified in genotype 1, into genotypes 2–6 parental and HVR1-deleted variants (not available for genotype 4a) we observed diverse effects on viral fitness and a universally pronounced reduction in AR5A sensitivity. Thus, we were able to take advantage of the neutralization-sensitive HVR1-deleted viruses to rapidly generate escape viruses aiding our understanding of the divergent escape pathways used by HCV to evade AR5A.